Common and Uncommon Psychological and Behavioral Situation in Applicants for Driving License Exempted from Military Service - Mehran Zarghami; Enayatollah Javadi; Soraya Sayar; Masoudeh Babakhanian (Journal of Mazandaran University of Medical Sciences, 2019)
Background and purpose: Some people are eligible for psychiatric exemptions before or during military service. This study aimed to investigate the common and uncommon psychological and behavioral situation in applicants for driving license exempt from military service. Materials and methods: In this cross-sectional study, the population included applicants for driving license with psychiatric disorders who were exempt from military service in Khuzestan, Lorestan and Ilam provinces, Iran 2015. The sample size was 585. Data were collected using the checklists provided by the medical commissions in The Law Enforcement Force of the Islamic Republic of Iran (NAJA) which was previously used by The General Department of NAJA with approval of the Ministry of Health. Data analysis was done in SPSS V21. Results: Among the applicants for driving license, 326 suffered mental disorders during military service and were exempted from military service. The disorders with highest frequency among the patients were seizure (31.5%) and mood disorders (29.2%). Among these individuals, 14.9% were banned from obtaining driving license, 63% were allowed to renew that, and 22% received treatment for mental disorders. The decisions for the driving license of the latter group were made after the treatment. Conclusion: Mood disorders were found to be the most prevalent psychiatric disorder among the applicants for driving license, so, necessary precautions should be taken when issuing or renewing the driving license to these people.